2015
DOI: 10.3109/0284186x.2015.1091499
|View full text |Cite
|
Sign up to set email alerts
|

A five-factor biomarker profile obtained week 4–12 of treatment for improved prognostication in metastatic renal cell carcinoma: Results from DARENCA study 2

Abstract: Background: Several biomarkers of treatment efficacy have been associated with a better prognosis in patients with metastatic renal cell carcinoma (mRCC). The prognostic significance of biomarkers in the early treatment phase is unclear. Material and methods: In a complete national cohort of mRCC patients receiving first-line tyrosine kinase inhibitors (TKI) or interleukin-2 based immunotherapy (IT) from 2006 to 2010, overall survival (OS) was analysed for baseline International mRCC Database Consortium (IMDC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The occurrence of sunitinib-induced hypertension has been shown to be associated with improved PFS and/or OS for patients with mRCC and has been proposed as an efficacy biomarker Rini et al reported objective response rates of 54.8% vs. 8.7%, median PFS of 12.5 (95% CI: 10.9–13.7) vs. 2.5 (95% CI: 2.3–3.8) months and OS of 30.9 (95% CI: 27.9–33.7) vs. 7.2 (95% CI: 5.6–10.7) months for patients developing sunitinib-related hypertension vs. patients without hypertension [ 46 ]. Similar effects were observed by additional studies, which also found that the co-occurrence of more than one AE (for example hand-foot-syndrome, neutropenia or thrombocytopenia) is an even stronger predictor of prolonged survival than hypertension alone [ 47 , 48 , 49 , 50 ].…”
Section: Therapy Of Renal Cell Carcinomasupporting
confidence: 76%
“…The occurrence of sunitinib-induced hypertension has been shown to be associated with improved PFS and/or OS for patients with mRCC and has been proposed as an efficacy biomarker Rini et al reported objective response rates of 54.8% vs. 8.7%, median PFS of 12.5 (95% CI: 10.9–13.7) vs. 2.5 (95% CI: 2.3–3.8) months and OS of 30.9 (95% CI: 27.9–33.7) vs. 7.2 (95% CI: 5.6–10.7) months for patients developing sunitinib-related hypertension vs. patients without hypertension [ 46 ]. Similar effects were observed by additional studies, which also found that the co-occurrence of more than one AE (for example hand-foot-syndrome, neutropenia or thrombocytopenia) is an even stronger predictor of prolonged survival than hypertension alone [ 47 , 48 , 49 , 50 ].…”
Section: Therapy Of Renal Cell Carcinomasupporting
confidence: 76%
“…Additionally, high preoperative NLR was associated with larger tumor size, higher nuclear grade, histologic tumor necrosis, and sarcomatoid differentiation [8]. Recently, on treatment neutropenia was shown to be an independent biomarker of favorable outcome in mRCC, independent of treatment type [11]. NLR was also recently shown to predict response to ipilimimab in melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some "toxicity" reflects on-target effect and is correlated with favorable outcome and should therefore not be avoided but should be acknowledged and appropriately treated. This is the case with hypertension, neutropenia, thrombocytopenia, hand-foot syndrome, [24][25][26][27] hypothyroidism, 28 and pneumonitis. 29 However, the most common adverse events to TKI associated with daily poor quality of life are fatigue, loss of appetite, diarrhea, nausea, and mucositis.…”
Section: Discussionmentioning
confidence: 97%